Regression equations for peak expiratory flow rate in children aged 5-10 years of Western Maharashtra, India: a cross-sectional study - Joshi, Sonal S.; Retharekar, Seemi A. (International Journal of Contemporary Pediatrics, 2023)
Background: Incidence of pulmonary diseases in urban children is on the rise. Peak expiratory flow rate, a component of pulmonary function tests, is a useful measure for initial pulmonary assessment. It is easily implementable on large population due to its simplicity. Studies presenting such data for Indian children are severely lacking, as PEFR is anthropometric, population and region specific. The present study aimed to establish an equation for predicting PEFR in urban children in Pune city in western Maharashtra, India. Methods: The cross-sectional study was done in Pune, Maharashtra, India. Children from different schools were selected by cluster sampling. The number of participants screened was 2100 of which 1760 were selected. Best of three readings of PEFR was recorded for each child using an EU Scale Peak Flow meter (Breath-O meter, Cipla). Anthropometric data like height, weight, chest expansion, waist/hip ratio were measured and BMI was calculated along with PEFR of each child. Results: Out of the 1760 children included in the study 933 (53%) were boys and 827 (47%) were girls. The stepwise regression analyses were carried out using age, height, weight and waist/hip ratio as predictor variables. Conclusions: Final regression equation was derived using height. Approximately 80% of the data was used for prediction of regression equation and remaining 20% data was used as a control group to validate the derived equation. The regression equation formulated shall offer a predicted PEFR value as guideline for healthcare workers in Pune city, Maharashtra, India.